204k views
5 votes
Use sigma notation to represent the following series for the first 10 terms. 3 + (-6) + 12 + (-24) + ⋯

User Laetis
by
4.9k points

1 Answer

4 votes

Answer:


$$\sum_(n=1)^(10) -3(-1)^(n) \hspace{3}2^(n-1) $$


n\in N

Explanation:

First, as you can see, the sequence is alternating its sign everytime, so you can deduce this term:


(-1)^(n)

The sequence start from 3, and the following terms are the product between 3 and
2^(n-1). Take a look:

For n=1


3*2^(1-1) =3*2^(0) =3*1=3

For n=2


3*2^(2-1) =3*2^(1) =3*2=6

And so on...

Let's verify the formula including all terms:

Since the sequence start from 3, we must change the 3 for -3. Because
(-1)^(n) is always negative for the first term:

For n=1


(-1)^(1) \hspace{3}-3*2^(1-1) =(-1)-3*2^(0) =(-1)-3*1=3

For n=2


(-1)^(2) \hspace{3}-3*2^(2-1) =(1)-3*2^(1) =(1)-3*2=-6

For n=3


(-1)^(3) \hspace{3}-3*2^(3-1) =(-1)-3*2^(2) =(-1)-3*4=12

For n=4


(-1)^(4) \hspace{3}-3*2^(4-1) =(1)-3*2^(3) =(1)-3*8=-24

So, one possible sequence is:


a_n=-3(-1)^(n) \hspace{3}2^(n-1)

And the serie would be given by:


$$\sum_(n=1)^(10) a_n $$ = $$\sum_(n=1)^(10) -3(-1)^(n) \hspace{3}2^(n-1) $$

User Blodrayne
by
5.4k points